The BLOCK DIAGRAM AND MATHEMATICAL MODEL OF AN INVARIANT SYSTEM: BLOCK DIAGRAM AND MATHEMATICAL MODEL OF AN INVARIANT SYSTEM - Куралов, Бекжон (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Recently, one of the modern directions of the theory of control, the theory of construction of state monitors of linear and nonlinear dynamic systems has significantly developed [2, 4, 10, 15]. The approach based on the expansion of the system dynamics based on the information of the input and output values due to the construction of a special dynamic system observer whose state converges quickly enough to the initial state of the system over time and the function of the state observer on the output, and the input of the initial system output variables and dynamic feedback can be applied spread out. In this case, the state observer at an arbitrary instant of time is considered as an estimate of the state of the system at a given instant of time [4]. Constructing an observer for a dynamic system is one of the ways to obtain an estimate of the state vector of this dynamic system. Solving such a problem can be of independent value as part of the general problem of dynamic systems control. The article considers the independence of the output value and the error signal from the input actions. In stabilization systems, it is necessary to add independence of the output value from the disturbing influence. The system is invariant with respect to the perturbing influence, if after the completion of the transient process determined by the initial conditions, the system error does not depend on this influence [12-16].